1972
DOI: 10.1073/pnas.69.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Triphosphatase Associated with Adenosine Triphosphate-Dependent Deoxyribonuclease

Abstract: An ATPase activity that is completely dependent on DNA is associated with the ATP-dependent DNase (recB-recC enzyme) purified from Escherichia coli.There is a strong correlation between the ATPase and the DNase activities under various assay conditions. With E. coli DNA as substrate, 8-9 molecules of ATP are hydrolyzed to ADP and inorganic phosphate for every phosphodiester bond hydrolyzed by the DNase. The possible functional relationship of the ATPase and DNase activities is discussed.We reported the partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1974
1974
1983
1983

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…The enzyme used here was prepared by the method of Nobrega et al (9), with omission of DEAE-cellulose chromatography.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme used here was prepared by the method of Nobrega et al (9), with omission of DEAE-cellulose chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…The recBC DNase and ATPase were assayed as described (9,10) and heat stability (half-life 30 min at 47.5°) as the original enzyme (data not shown). These results suggested that the DNase molecules were dissociated into two subunits by the NaCl treatment and that active enzvme molecules were reconstituted when these subunits were recombined.…”
Section: Methodsmentioning
confidence: 99%
“…The inactivation of ATP-dependent DNase during DEAE-cellulose chromatography was observed by several authors [10,15,17,20,31,32]. The extent of inactivation differed, depending on the chromatographic resolutions used.…”
mentioning
confidence: 96%
“…Enzymes which degrade ATP to ADP and Pi using DNA as cofactur have been detected in both prokaryotic El- 31 and eukaryotic cells [4,5]. Several publications deal witb enzymatic reactions implied in replication and recombination of the genetic material in which ~NA-dependent hydrolysis of ATP occurs [1,2,3,6].…”
Section: ; Intr~~~ctiunmentioning
confidence: 99%
“…This genetic exchange of preexisting intact DNA scqucnces is accompanied by DNA repair synthesis at the insertion sites [50,51]. It has been shown that the recombinational genes involved, recB and recC, specify and ATP-dependent nuclease [52] (exonuclease V) which degrades single-stranded and duplex DNA in the 3' + 5' and 5' --t 3' directions. The ATP requirement of the (Ac),ONFln-induced and 7-bromomethylbenz[u]anthracene-induced DNA synthesis could indicate the involvement of this enzyme in the DNA exchange process, e.g., in expanding post-replication gaps before donor strands are inserted.…”
Section: Influence Of Rec Gene Mutationsmentioning
confidence: 99%